USING LANGUAGE SITUATION AS AN EFFECTIVE METHOD DEVELOPMENT OF CONVERSATIONAL LANGUAGE IN ENGLISH EDUCATION - G. A. Djumaeva (American Journals, 2022)
The analysis of the history and change of approaches in teaching a foreign language to students of higher education institutions clearly shows the importance of focusing on teaching speaking as one of the main types of speech activity, which means using primarily a communicative teaching method in their work.
Keywords: teaching speaking, natural communication situations, dialogue relationships.